Partai Islam dan Pemilih Islam di Indonesia - Romli, Lili (Jurnal Penelitian Politik, 2004)
The resurgent of Islamic parties occurs in the reform era because of many factors which are theological, sociological, historical, reformation and democratization. Unfortunately the resurgent of Islamic parties cannot be endorsed by the Islamic voters. This can be seen from a small and unsignificant vote reached by the Islamic parties. In the 1999 general election, the Islamic parties only have !7,8 percent vote and in the 2004 general election only have 21,17percent vote. This small and unsignificant vote of the Islamic parties happened because of fragmentation of Islamic parties and ideological orientation change of Islamic voters.